Stink and the ultimate thumb-wrestling smackdown - McDonald, Megan; Reynolds, Peter, 1961- (Somerville, Mass. : Candlewick Press, 2011)
After second-grader Stink gets an unsatisfactory grade in physical education, his parents tell him he must play a sport and so he masters thumb wrestling, as seen on a sports channel.
Keywords: Schools -- Juvenile fiction; Families -- Juvenile fiction; Sports stories; Humorous fiction